Pendidikan Islam dalam Pendekatan Multidisipliner: Suatu Pengantar Kajian Gradual Menuju Paradigma Global - Mukhamad Ilyasin (Institut Agama Islam Negeri (IAIN) Samarinda, 2010)
History of Islamic education is still using the conventional approach which is generally a diachronic study centered on the history of ideas of great thinkers and leaders in education, or history and the educational system and also the institutions, or the history of legislation and public policy in education. Diachronic approach that generally is considered to be static, narrow and too inward looking. Accordingly, there should be an approach to history education (Islam) which just is not enough to just diachronic ways. There should be a new methodological approach with an interdisciplinary approach. Islamic education will need to use a combination approach is diachronic approach history with a synchronic social sciences are sociology and anthropology to bring its characteristics and also the characters. This interdisciplinary approach is holistic, integrative approach based on the components of the nature and pattern of education should be integrated in the curriculum of Islamic education as a first step towards undikotomic educational paradigm which is the natural child of the conventional approach is diachronic approach.